Lumbar puncture for neurosyphilis investigation in asymptomatic patients with HIV-syphilis coinfection: a cross-sectional study among infectious disease specialists - Henriques, Bárbara Labella; Vidal, José Ernesto; Gamba, Cristiano; Silva, Vivian Iida Avelino (São Paulo Medical Journal, 2023)
BACKGROUND: Syphilis is a major public health issue worldwide. In people living with human immunodeficiency virus (PLHIV), there are higher incidences of both syphilis and neurosyphilis. The criteria for referring PLHIV with syphilis for lumbar puncture is controversial, and the diagnosis of neurosyphilis is challenging. OBJECTIVE: To describe the knowledge, attitudes, and practices of infectious disease specialists and residents in the context of care for asymptomatic HIV-syphilis coinfection using close-ended questions and case vignettes. DESIGN AND SETTING: Cross-sectional study conducted in three public health institutions in São Paulo (SP), Brazil. METHODS: In this cross-sectional study, we invited infectious disease specialists and residents at three academic healthcare institutions to answer a self-completion questionnaire available online or in paper form. RESULTS: Of 98 participants, only 23.5% provided answers that were in line with the current Brazilian recommendation. Most participants believed that the criteria for lumbar puncture should be extended for people living with HIV with low CD4+ cell counts (52.0%); in addition, participants also believed that late latent syphilis (29.6%) and Venereal Disease Research Laboratory (VDRL) titers ≥ 1:32 (22.4%) should be conditions for lumbar puncture in PLHIV with no neurologic symptoms. CONCLUSION: This study highlights heterogeneities in the clinical management of HIV-syphilis coinfection. Most infectious disease specialists still consider syphilis stage, VDRL titers and CD4+ cell counts as important parameters when deciding which patients need lumbar puncture for investigating neurosyphilis.